Dispersal Limitation Plays Stronger Role in the Community Assembly of Fungi Relative to Bacteria in Rhizosphere Across the Arable Area of Medicinal Plant - Zhang, Guozhuang; Wei, Guangfei; Wei, Fugang; Chen, Zhongjian; He, Mingjun; Jiao, Shuo; Wang, Yong; Dong, Linlin; Chen, Shilin (Frontiers in Microbiology, 2021)
Understanding the ecological patterns of rhizosphere microbial communities is critical for propelling sustainable agriculture and managing ecosystem functions by exploiting microorganisms. However, this knowledge is still unclear, especially under host-associated large-scale and regarding the comparison between bacteria and fungi. We examined community assembly processes and community characters including environmental thresholds and co-occurrence patterns across the cultivatable area of Panax notoginseng for bacteria and fungi. Both are vital members of the rhizosphere but differ considerably in their life history and dispersal potentiality. Edaphic factors drove the parallel variations of bacterial and fungal communities. Although bacterial and fungal communities exhibited similar biogeographic patterns, the assembly of fungi was more driven by dispersal limitation than selection compared with bacteria. This finding supported the ‘size-dispersal’ hypothesis. pH and total nitrogen respectively mediated the relative importance of deterministic and stochastic processes in shaping bacterial and fungal communities. In addition, fungal communities exhibited potentially broader environmental thresholds and more modular co-occurrence patterns than bacteria (bacteria: 0.67; fungi: 0.78). These results emphasized the importance of dispersal limitation in structuring rhizosphere microbiota and shaping community features of ecologically distinct microorganisms. This study provides insights into the improved prediction and management of the key functions of rhizosphere microbiota.